Estimating Energy Demand Elasticities for OECD Countries. A Dynamic Panel Data Approach - Gang Liu (Statistics Norway, Research Department, 2004)
This paper estimates price and GDP/income elasticities of several energy goods in OECD countries over 1978 to 1999 by applying the one-step GMM estimation method suggested by Arellano and Bond (1991) to a panel data set. The energy demand is specified by a simple partial adjustment model. We find that compared to conventional OLS and Within estimator, the one-step GMM estimator gives more intuitive results in terms of sign and magnitude. The results show that for electricity, natural gas and gas oil demand, price elasticities are in general larger (in absolute value) while GDP/income elasticities are lower in the residential sector than in the industrial sector. This paper yields lower values for price elasticities compared to the results from earlier studies. The long-run GDP/income elasticities found in this paper, however, are quite similar to those found in earlier studies, and are around unity in general.
Keywords: C23; Q41; 330; Energy demand elasticities; Panel data; ADL models; Partial adjustment model; One-step GMM estimator